A Descriptive Study On Teaching Vocabulary To The Fifth Year Students Of SD N 2 Ngrendeng Ngawi In 2011 / 2012 Academic Year - Desiana, Ettyk (2012)
This research aims at describing the techniques of teaching vocabulary to the fifth year students of SD N 2 Ngrendeng Ngawi. The objectives of this research paper are to describe: (1) the techniques of teaching vocabulary in SD N 2 Ngrendeng Ngawi, (2) the problems faced by the teacher and the students in teaching learning English vocabulary, (3) the strategies used by teacher to solve the students' difficulties This research is descriptive qualitative. The subject of the research is English teachers and the fifth year students in SD N 2 Ngrendeng Ngawi. While the object of this research is teaching vocabulary to the fifth year students of SD N 2 Ngrendeng, Ngawi in 2011 / 2012 academic year. The Writer uses descriptive method as the method of collecting data in this study by employing observation, interview, and document. Based on the result of the analysis, the writer finds that the teaching techniques implemented by the teacher to the fifth year students in SD N 2 Ngrendeng Ngawi, are translation, picture and draw the sketch, example- illustration clues, quiz, and memorize vocabulary. Besides, the problems faced by the teacher in teaching learning vocabulary to the fifth year student of SD N 2 Ngrendeng, Ngawi are time management, limited vocabulary and pronunciation. The students got difficulties to respond the material and have less motivation, while the problems faced by the fifth year students are the students have limited vocabulary and pronunciation, understand to accept material. The teacher implemented two strategies to solve students' difficulties such as the teacher giving motivation and giving reward